Sensitivity of Neuroimaging Indicators in Monitoring the Effects of Interferon Gamma Treatment in Friedreich’s Ataxia - Vavla, Marinela; Arrigoni, Filippo; Toschi, Nicola; Peruzzo, Denis; D’Angelo, Maria Grazia; Gandossini, Sandra; Russo, Annamaria; Diella, Eleonora; Tirelli, Stefania; Salati, Roberto; Rufini, Alessandra; Condo, Ivano; et al. (Frontiers in Neuroscience, 2020)
The identification of efficient markers of disease progression and response to possibly effective treatments is a key priority for slowly progressive, rare and neurodegenerative diseases, such as Friedreich’s ataxia. Various imaging modalities have documented specific abnormalities in Friedreich’s ataxia that could be tracked to provide useful indicators of efficacy in clinical trials. Advanced MRI imaging (diffusion tensor imaging, DTI; functional MRI, fMRI; and resting-state fMRI, rs-fMRI) and retinal imaging (optical coherence tomography, OCT) were tested longitudinally in a small group of Friedreich’s ataxia patients participating in an open-label clinical trial testing the safety and the efficacy of 6-month treatment with interferon gamma. While the DTI indices documented the slow progression of fractional anisotropy loss, fMRI and rs-fMRI were significantly modified during and after treatment. The fMRI changes significantly correlated with the Scale for the Assessment and Rating of Ataxia, which is used to monitor clinical response. OCT documented the known thickness reduction of the retinal nerve fiber layer thickness, but there was no change over time. This pilot study provides indications for the potential utility of fMRI and rs-fMRI as ancillary measures in clinical trials for Friedreich’s ataxia.